2021
DOI: 10.1371/journal.pcbi.1009547
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the HydroxyMethylCytosine epigenetic signature on DNA structure and function

Abstract: We present a comprehensive, experimental and theoretical study of the impact of 5-hydroxymethylation of DNA cytosine. Using molecular dynamics, biophysical experiments and NMR spectroscopy, we found that Ten-Eleven translocation (TET) dioxygenases generate an epigenetic variant with structural and physical properties similar to those of 5-methylcytosine. Experiments and simulations demonstrate that 5-methylcytosine (mC) and 5-hydroxymethylcytosine (hmC) generally lead to stiffer DNA than normal cytosine, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 83 publications
(122 reference statements)
1
11
0
Order By: Relevance
“…In general, hmC is considered to reverse the impacts of methylation on DNA physical properties. Numerous studies have shown that while mC increases the duplex melting temperature, hmC brings it back closer to the one observed with C. 68,126,127,129…”
Section: Structure and Interactions Of Hmc-dnasupporting
confidence: 56%
See 3 more Smart Citations
“…In general, hmC is considered to reverse the impacts of methylation on DNA physical properties. Numerous studies have shown that while mC increases the duplex melting temperature, hmC brings it back closer to the one observed with C. 68,126,127,129…”
Section: Structure and Interactions Of Hmc-dnasupporting
confidence: 56%
“…In general, hmC is considered to reverse the impacts of methylation on DNA physical properties. Numerous studies have shown that while mC increases the duplex melting temperature, hmC brings it back closer to the one observed with C. 68,126,127,129 A single-molecule mechanical force study showed that the mechanical stability of DNA (resistance to zipper-mode strand separation) increases with the number of hmC bases. 137 Different approaches have been taken to evaluate the effects of epigenetic DNA modifications on the DNA flexibility with anticipation of finding a direct mechanistic connection to nucleosome binding and gene expression regulation.…”
Section: Single-molecule Long Read Biophysical Detectionmentioning
confidence: 69%
See 2 more Smart Citations
“…A series of molecular dynamics simulation research studies and experiments have studied the effect of methylation on the physical properties and dynamic features of DNA. Battistini et al performed molecular dynamics simulations, biophysical experiments, and NMR spectroscopy to study the impact of 5-hydroxymethylation on DNA cytosine and demonstrated that the modified cytosines (5mC or 5hmC) made the DNA stiffer than the normal cytosine [ 76 ]. Further studies performed by Hognon et al also explained how different levels of methylation in CpG sites affect the behavior of DNA [ 77 ].…”
Section: Multiple Regulatory Factors and Associated Mechanismmentioning
confidence: 99%